The nonlinear feedback dynamics of asymmetric political polarization - Leonard, Naomi Ehrich; Lipsitz, Keena; Bizyaeva, Anastasia; Franci, Alessio; Lelkes, Yphtach (Proceedings of the National Academy of Sciences - PNAS, 2021)
Using a general model of opinion dynamics, we conduct a systematic investigation of key mechanisms driving elite polarization in the United States. We demonstrate that the self-reinforcing nature of elite-level processes can explain this polarization, with voter preferences accounting for its asymmetric nature. Our analysis suggests that subtle differences in the frequency and amplitude with which public opinion shifts left and right over time may have a differential effect on the self-reinforcing processes of elites, causing Republicans to polarize more quickly than Democrats. We find that as self-reinforcement approaches a critical threshold, polarization speeds up. Republicans appear to have crossed that threshold while Democrats are currently approaching it.